2017
DOI: 10.3390/min7110226
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Prediction of Bulk Gold Fineness at Placer Gold Mines: A New Zealand Example

Abstract: This study documents the bulk Au fineness (Au parts per thousand) of the bullion from a placer gold mine in southern New Zealand. The compositions of doré bars produced approximately every 10 days over nearly three years is compared to the range of compositions of gold particles which have been extracted. Silver is the principal impurity in the gold, and the doré bars contained 2-3 wt % Ag over the period examined. At the scale of a typical individual 0.5 mm gold particle, there are three different types of go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…3I), but have seen no evidence that gold accumulation is progressive beyond these features. Consequently, we concur with Stewart et al (2017) and Craw et al (2017), who made a clear distinction between surface authigenic gold and a pre-existing rim formed by Ag depletion.…”
Section: Post-depositional Modification: Surficial Environmentsupporting
confidence: 90%
“…3I), but have seen no evidence that gold accumulation is progressive beyond these features. Consequently, we concur with Stewart et al (2017) and Craw et al (2017), who made a clear distinction between surface authigenic gold and a pre-existing rim formed by Ag depletion.…”
Section: Post-depositional Modification: Surficial Environmentsupporting
confidence: 90%
“…The homogeneous chemical composition of the detrital gold present in the matrix of the metaconglomerate, including the narrow range of silver contents, indicates a single source, or sourcing from a single deposit class (e.g., Craw et al 2017), although multiple sources could be expected for a paleoplacer deposit, considering that the provenance study (Klein et al 2017) showed multiple sources for detrital zircon of the hosting metaconglomerate. The high Au/Ag ratios and absence of significant content of any other metal suggest that the gold particles might have come from orogenic gold source(s) (Minter 1991).…”
Section: Source Of the Detrital Goldmentioning
confidence: 99%
“…Chemical alteration to gold particle cores can occur during annealing following deformation as described above (Stewart et al 2017;McLachlan et al 2017;Kerr et al 2017b), and in our view is the most common origin of gold particles which appear to have multiple cores, such as illustrated by Knight et al (1999a). Some researchers view the addition of a gold rim to pre-existing particles as the first stage in a process of biologically mediated 'transformation'.…”
Section: Alteration Of Core Alloy Compositionmentioning
confidence: 91%
“…6a-c). Similarly, a mixture of gold particle morphologies can also occur in modern placers where gold Craw et al 2017). The progressive nature of gold particle deformation has been studied in the context of transport distance both qualitatively (Townley et al 2003) and quantitatively (e.g.…”
Section: Formationmentioning
confidence: 99%
See 1 more Smart Citation